(untitled) (CIPEEX, 2025)
INTRODUCTION: Metabolic dysfunction-associated steatohepatitis (MASH) is a chronic liver disease that can progress to compensated cirrhosis. This condition represents an important cause of morbidity, with no approved therapies for advanced stages. Efruxifermin, an analog of fibroblast growth factor 21 (FGF21), has shown therapeutic potential due to its anti-inflammatory, anti-fibrotic, and metabolic effects. OBJECTIVE: To evaluate the efficacy and adverse events of efruxifermin at two different dosages in the treatment of patients with MASH and advanced liver fibrosis. METHODS: A systematic review and meta-analysis of randomized clinical trials was conducted using PubMed and Cochrane databases. Four studies out of 172 screened were included, comparing 28 mg and 50 mg doses of efruxifermin with each other or with placebo and reporting at least one outcome of interest. The outcomes assessed were ≥1 stage improvement in fibrosis without worsening of MASH and the occurrence of adverse events such as nausea and diarrhea. Statistical analyses were performed using RevMan 5.4. Relative risks (RR) with 95% confidence intervals (CI) were calculated for dichotomous variables, using a random-effects model. RESULTS: A total of 419 patients were evaluated, of whom 284 (68%) received efruxifermin. Both 50 mg and 28 mg doses were significantly superior to placebo in improving fibrosis by ≥1 stage without worsening of MASH (RR 1.70; 95% CI 1.07–2.70; p = 0.03 and RR 1.69; 95% CI 1.06–2.70; p = 0.03, respectively; I² = 0%). Regarding safety, no significant differences were found between the 50 mg and 28 mg doses in the incidence of nausea (RR 0.77; 95% CI 0.49–1.22; p = 0.27; I² = 35%) or diarrhea (RR 1.69; 95% CI 0.53–1.11; p = 0.16; I² = 28%). CONCLUSION: Both doses of efruxifermin demonstrated efficacy in improving fibrosis, with an acceptable safety profile. Nausea and diarrhea were the most common adverse events, generally mild and without significant differences between doses.